Meningkatkan Nilai Kearifan Lokal melalui Implementasi Program P5 Silek Tuo Pagaruyung - Elvi Deswita; Fadhilah Rahmafitri; Asmendri Asmendri; Milya Sari (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
The Merdeka Curriculum is an educational innovation introduced to address educational problems in Indonesia, one of which is the decline in cultural values and local wisdom eroded by outside cultural influences. The P5 programme or the Pancasila Student Profile Strengthening Project has chosen local wisdom as one of its focuses, with the aim of re-exploring cultural values and local wisdom that may have been forgotten. This research was conducted to describe the process of increasing local wisdom values through the implementation of the P5 Silek Tuo Pagaruyung programme. This research method is qualitative field research with an analytical descriptive approach. Data were collected through observation, interviews, and documentation, then analysed using the Miles and Hubberman technique, which involves data reduction, data verification, and conclusion drawing. The results showed that the implementation of the P5 programme involved several stages, including planning, implementation, project assessment, and reporting and evaluation. The success of this programme is reflected in the implementation of values by students, such as spiritual values, movement arts, martial arts, and sports.